2000
DOI: 10.1016/s0029-7844(99)00543-8
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in term infants: a population-based study

Abstract: Immunologic studies should be considered in all cases of severe neonatal thrombocytopenia for careful monitoring and prevention of potentially severe complications in subsequent pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 17 publications
4
71
0
7
Order By: Relevance
“…24 Also, this study confirmed that the CB PLT count is higher after vaginal delivery than after Cesarean section. 25 Recently, PLT count and MPV reference ranges for the first 3 days of life were reported for neonates in a large, multi-hospital study.…”
Section: Discussionsupporting
confidence: 76%
“…24 Also, this study confirmed that the CB PLT count is higher after vaginal delivery than after Cesarean section. 25 Recently, PLT count and MPV reference ranges for the first 3 days of life were reported for neonates in a large, multi-hospital study.…”
Section: Discussionsupporting
confidence: 76%
“…After critical appraisal of the full text of the remaining 21 articles independently by 2 authors (MK and NP), 6 studies were included in the review. 1,2,[8][9][10][11] The main reason for exclusion was that screening was not performed in a low-risk population but in newborns selected by the history of siblings who suffered from fetal and neonatal alloimmune thrombocytopenia (FNAIT) during pregnancy or at birth. Another important reason for exclusion was the use of case finding through maternal HPA-1a typing in unselected pregnant women, with further analysis in those women who were typed negative for HPA-1a.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…The other 3 studies focused on neonatal thrombocytopenia. 1,8,10 One study analyzed 2 control groups to identify the incidence of alloimmunization in respectively thrombocytopenic mothers of nonthrombocytopenic newborns and nonthrombocytopenic mothers of nonthrombocytopenic newborn. 2 The difference was statistically significant between the group of mothers with thrombocytopenic newborns and the control groups but not between the 2 control groups Only 1 paper reported a sample size calculation 1 ; all the others chose a fixed time period, varying from 1 to 7 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerated consumption of thrombocytes and their sequestration from blood are the main causes of 25% to 35% neonatal thrombocytopenia. Out of all thrombocytopeniae manifested at birth, 15% to 20% are result of transplacental transmission of mother's antibodies, and disseminated intravascular coagulation, which is responsible for the remaining 10% to 15% cases, almost always occurs in the newborn with poorer clinical status and is connected with prenatal asphyxia and infection [3][4][5]. The newborn may develop thrombocytopenia due to various neonatal complications, such as: infection, perinatal asphyxia, respiratory distress syndrome, polycythaemia and necrotizing enterocolitis.…”
Section: Introductionmentioning
confidence: 99%